The Impact Of Hasyim Asy’ari On Shaping The Tradition Of Hadith Study In Nusantara - Andi Muhamad Hidayat; Dadah Saadah; Mubin Olatoye Raji; Khalid Hussain Mir (Cakrawala: Journal of Religious Studies and Global Society, 2025)
The 20th century marked an important phase in the development of hadith studies in the archipelago, especially in the face of the challenges of modernity and the current of renewal of Islamic thought. In the midst of these dynamics, KH. M. Hasyim Asy'ari appears as a central figure who plays a strategic role in strengthening the authority of hadith as a source of Islamic teachings. Through his monumental work Risalah Ahl al-Sunnah wa al-Jama'ah, Hasyim Asy'ari not only affirmed the position of hadith in the Islamic scientific system, but also offered a contextual methodological approach to the religious reality of Indonesian society at that time. This research uses a qualitative-descriptive approach with a content analysis method, which is focused on a systematic review of the content of the book Risalah Ahl al-Sunnah wa al-Jama'ah. The analysis is directed to identify the construction of Hasyim Asy'ari's thoughts on hadith, as well as to trace how his work contributes to the formation of the scientific tradition of hadith in Indonesia, especially in the pesantren environment. The results of the study show that Hasyim Asy'ari's hadith thinking is based on the spirit of maintaining the authority of sanad, purifying the creed from the influence of extreme thought, and strengthening the framework of Ahlussunnah wal Jama'ah as the epistemological basis for hadith studies in Indonesia. His moderate attitude, firm in faith, and adaptive to the Indonesian social context made his hadith thought a meeting point between classical heritage and the needs of the times. The work also forms the pattern of Islamic boarding school hadith study which is characterized by a balance between text and context, between sanad and the benefit of the ummah. Thus, it can be concluded that Hasyim Ash'ari's contribution to the study of hadith in the archipelago is not only theological, but also epistemological and methodological. His thinking provides a solid foundation for the development of hadith studies in Indonesia, as well as an important reference in responding to contemporary Islamic challenges. This study emphasizes the urgency of preserving and developing the intellectual heritage of local scholars such as Hasyim Asy'ari in formulating an authentic, contextual, and sustainable paradigm of Islamic science.